Betainium-based ionic liquids catalyzed multicomponent Hantzsch reactions for the efficient synthesis of acridinediones. Issue 11 (20th January 2017) - Zhu, Anlian; Liu, Ruixia; Du, Chunyan; Li, Lingjun
Abstract : Betainium lactate was found to be an efficient catalyst for the Hantzsch reactions under mild conditions. Abstract : In this study, a series of betainium-based ionic liquids with various anions have been synthesized and their catalytic performances for the Hantzsch reactions have been investigated. It is shown that these ionic liquids have high selectivity for the one-pot production of acridinediones through Hantzsch reactions under mild conditions, and betainium lactate has the highest catalytic activity. This ionic liquid catalyst is very cheap and easy to prepare; the catalytic procedure is very simple and the catalyst can be recycled and reutilized. In addition, the biocompatibility of the raw material of these ionic liquids suggests that this catalytic system may have great industrial potential applications.